MAPPING INTERNATIONAL SOURCES OF FUNDING FOR CULTURAL AND EDUCATIONAL PROJECTS IN NORTHEASTERN BRAZIL - da Silva, Jonnas Costa (Seven Editora, 2025)
This article maps the international sources of funds for cultural (including the conservation of historical heritage) and educational projects in Brazil, with an emphasis on the Northeast region, in the period from 2021 to the present. Following a documentary research methodology, multilateral development banks, bilateral cooperation agencies and international non-governmental organizations (NGOs) active in the financing of these projects were identified. The sources of financing are classified by type of support – repayable loans, non-repayable grants, and technical cooperation – according to the guidelines of the Mapping Development Finance Institutions Worldwide report by Xu et al. (2019). The results include tables listing types of institutions and modalities of support, as well as concrete examples of internationally supported cultural and educational projects, highlighting the volume and nature of investments destined to the Northeast. The analysis indicates that while development banks account for the largest volumes of resources (mainly via loans) in education and culture, grantmaking partnerships and technical cooperation play a crucial role in strengthening institutions and reaching vulnerable communities. There is a significant concentration of international initiatives in northeastern states, given the regional socioeconomic disparities, including educational programs of municipal scope and cultural preservation projects. Finally, the article discusses implications for public management and provides subsidies for the visualization in a conceptual map of the relationships between funding sources and support modalities. DOI: https://doi.org/10.56238/sevened2025.030-007